Access to HIV-related Services Among Short-distance Drivers in India: Insights from a Qualitative Study - Priyanka Dixit; Supriya Lahoti; Arpana Kullu; Chinmoyee Das; Shobini Rajan; Bhawani Singh Kushwaha; Saiprasad Bhavsar; Vinita Verma; Shantanu Purohit (Journal of Psychosexual Health, 2025)
Objectives: There is a significant gap in evidence regarding the health-seeking behaviour of short-distance drivers (SDDs) traveling less than 800 km in a single direction within India, resulting in an absence of healthcare programmes or interventions specifically designed for this group. This exploratory qualitative assessment was conducted to understand the experiences and perceptions of SDDs regarding health services available for human immunodeficiency virus (HIV). Methods: In-depth interviews were conducted in 2022 with 86 primary and 118 secondary participants from nine states in India. The interviews were conducted in five different languages. Two separate interview guides were developed: one for primary participants (including drivers) and another for secondary participants (such as government officials, programme officials and nongovernment organisation [NGO] representatives). Purposive sampling was employed to select secondary participants, while primary participants were identified through snowball sampling. Data analysis was carried out using thematic analysis, identifying key themes and patterns from the transcripts. ATLAS.ti (version 8) software was used for data analysis. Results: The SDDs did not have knowledge of any HIV prevention or care services accounting for their working environment and hours. The results showed that financial problems, poor management of healthcare services, lack of knowledge regarding the available services and quality of care at public healthcare facilities were major barriers to accessing care for HIV/AIDS. The perceived risk of infection did not translate into seeking testing for HIV. Stigma emerged as an important factor that deterred testing as well as treatment for HIV/AIDS. The secondary participants mentioned that the targeted interventions had limited engagement with short-distance drivers due to a lack of specific focus on this group. Conclusion: This study highlights the need for tailored HIV prevention and care programmes for SDDs, who face unique barriers such as financial constraints, stigma and limited healthcare access. It emphasises the importance of integrating this group into national strategies to improve awareness, reduce stigma and promote regular testing.